Prinsip Akad Asuransi Syariah dalam Perspektif Hukum Islam - Thabrani Rosyidi (Fakultas Hukum Universitas Islam Jember, 2014)
Economic activity is generally carried out by economic actors both individuals who run the company or not a business entity that has a good standing as a corporation or a legal entity. Economic activity is essentially running the company activity that is, an activity which implies that the activity in question should be carried out continuously in the sense of not falter, openly in a legal sense (not illegal), and they are carried out in order gain either for themselves or others. For the economic activities as the main requirement in supporting the survival of the community in the form of investment activities are managed by financial institutions. The existence of financial institutions is as an institution that provides financial services to its customers.vity is generally carried out by economic actors both individuals who run the company or not a business entity that has a good standing as a corporation or a legal entity